AutoWebS: um Ambiente para Modelagem e Geração Automática de ServiçosWeb Semânticos - Silva, Thiago Pereira da (2012)
Typically Web services contain only syntactic information that describes their interfaces. Due to the lack of semantic descriptions of the Web services, service composition becomes a difficult task. To solve this problem, Web services can exploit the use of ontologies for the semantic definition of service s interface, thus facilitating the automation of discovering, publication, mediation, invocation, and composition of services. However, ontology languages, such as OWL-S, have constructs that are not easy to understand, even for Web developers, and the existing tools that support their use contains many details that make them difficult to manipulate. This paper presents a MDD tool called AutoWebS (Automatic Generation of Semantic Web Services) to develop OWL-S semantic Web services. AutoWebS uses an approach based on UML profiles and model transformations for automatic generation of Web services and their semantic description. AutoWebS offers an environment that provides many features required to model, implement, compile, and deploy semantic Web services